Networking know-how [online networking]. - Karlin, S.
This paper discusses the latest trend in online job hunting and hiring, i.e. tapping social and professional networking sites. These sites typically allow you to post a profile, listing information about yourself as well as services and skills you have to offer. Reciprocal connections can also be made between the profiles of different users, allowing for friend-of-a-friend style introductions. These sites also enable people to forge long-term business relationships around outside interests and skill sets. This paper provides a few tips on how to get the most out of online networking.
Keywords: Friend-of-a-friend style introductions; Job hiring; Long-term business relationships; Online job hunting; Online networking; Reciprocal connections